2012
DOI: 10.1111/acel.12014
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stromal cell and sarpogrelate orchestrate the recovery of inflammation‐induced angiogenesis in aged hindlimb ischemic mice

Abstract: SummaryAging population displays a much higher risk of peripheral arterial disease (PAD) possibly due to the higher susceptibility, poor prognosis, and fewer therapeutic options. This study was designed to examine the impact of combined multipotent adipose‐derived stromal cells (mADSCs) and sarpogrelate treatment on aging hindlimb ischemia and the mechanism of action involved. mADSCs (1.0 × 107) constitutively expressing enhanced green fluorescent protein (eGFP) or firefly luciferase (Fluc) reporter were engra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…1C). mADSCs Fluc + GFP + were positive for MSC markers CD90, CD44 and exhibited low expression of endothelial (CD34) and leukocyte markers (CD45), which represented the potential of differentiating into adipocytes and osteogenic cell lineages, as shown in our previous work (7). Furthermore, real-time quantitative PCR (RT-qPCR) and Western blot analysis revealed that the mRNA and protein expression of LXR a and LXR b were present in mAD-MSCs (Fig.…”
Section: Mad-mscssupporting
confidence: 66%
See 2 more Smart Citations
“…1C). mADSCs Fluc + GFP + were positive for MSC markers CD90, CD44 and exhibited low expression of endothelial (CD34) and leukocyte markers (CD45), which represented the potential of differentiating into adipocytes and osteogenic cell lineages, as shown in our previous work (7). Furthermore, real-time quantitative PCR (RT-qPCR) and Western blot analysis revealed that the mRNA and protein expression of LXR a and LXR b were present in mAD-MSCs (Fig.…”
Section: Mad-mscssupporting
confidence: 66%
“…Other studies demonstrated that improving the conditions of this unfavorable niche in infarcted myocardium could increase the survival of injected stem cells (31,39). Our group also found that regulating local inflammation in ischemic tissue with sarpogrelate could enhance engrafted AD-MSCs viability and antiapoptotic/proangiogenic efficacy in vivo (7). In addition to microenvironmental regulation, increasing the stem cells' ability to resist local stress, such as local inflammation and oxidative stress, is also crucial for stem cell survival and efficacy (22,37).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, the therapeutic efficacy has been held back by the poor survival of donor cells 3 . Our previous findings also demonstrated the feasibility of utilizing adipose derived mesenchymal stem cells (AD-MSCs) in the management of PAD courtesy of its multipotency, abundance for harvest and low immunogenicity 4 . However, low survival rate has been identified for the transplanted AD-MSCs within ischemic tissues, hampering the advancement of AD-MSCs in the therapeutics of PAD 4 .…”
mentioning
confidence: 85%
“…Our previous findings also demonstrated the feasibility of utilizing adipose derived mesenchymal stem cells (AD-MSCs) in the management of PAD courtesy of its multipotency, abundance for harvest and low immunogenicity 4 . However, low survival rate has been identified for the transplanted AD-MSCs within ischemic tissues, hampering the advancement of AD-MSCs in the therapeutics of PAD 4 . To this end, it is pertinent to search for new and novel approaches to promote donor cell survival in order to foster the success of stem cell-based therapy for PAD.…”
mentioning
confidence: 85%